Toxic Positivity in Feminist Discourse: A Critical Discourse Analysis of Shiza Shahid’s TED Talk - Nawaz, Muhammad Shafqat; Qasim, Hafiz Muhammad (Pakistan Languages and Humanities Review, 2025)
This paper explores the discursive construal of toxic positivity in the TED Talk by Shiza Shahid. The study aims to determine transitivity patterns, processes and participants, and explains how they linguistically build toxic positivity, further explaining them in socio- cultural settings. The study applied both the Transitivity Model of Halliday (1985) for textual analysis and the three-dimensional model of Critical Discourse Analysis of Fairclough (1989) to the interpretation and explanation of a text. The results showed that most of the processes were Material, Relational, and Mental, which describe self-belief, moral strength, and emotional composure as alternatives to structural critique and thus linguistically construe toxic positivity. The work is relevant to discourse analysts, feminist scholars, and communication researchers because it helps shed light on how motivational feminist discourse can propagate the false hope and make endurance a moral obligation instead of a right of the group.